2005
DOI: 10.1002/ijc.21445
|View full text |Cite
|
Sign up to set email alerts
|

Indole‐3‐carbinol activates the ATM signaling pathway independent of DNA damage to stabilize p53 and induce G1 arrest of human mammary epithelial cells

Abstract: The phytochemical indole-3-carbinol (I3C), from cruciferous vegetables such as broccoli, has been shown to elicit a potent anti-proliferative response in human breast cancer cell lines. Treatment of the immortalized human mammary epithelial cell line MCF10A with I3C induced a G1 cell cycle arrest, elevated p53 tumor suppressor protein levels and stimulated expression of downstream transcriptional target, p21. I3C treatment also elevated p53 levels in several breast cancer cell lines that express mutant p53. I3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 53 publications
3
57
0
3
Order By: Relevance
“…This information is detailed in SI Text. The flow cytometry was performed as we previously described (15), and the Western blots, cyclin E immunoprecipitations, and assays of CDK2 enzymatic activity using histone H1 as a substrate were carried out as described (29).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This information is detailed in SI Text. The flow cytometry was performed as we previously described (15), and the Western blots, cyclin E immunoprecipitations, and assays of CDK2 enzymatic activity using histone H1 as a substrate were carried out as described (29).…”
Section: Methodsmentioning
confidence: 99%
“…In estrogen-responsive breast cancer cells, I3C suppresses estrogen responsiveness (13,14), down-regulates expression of estrogen receptor-␣ (13), and synergizes with the antiproliferative effects of tamoxifen, an anti-estrogen widely used in breast cancer therapies (10). In nontumorigenic human mammary epithelial cells, I3C can induce the ATM signaling pathway independent of DNA damage to stabilize an active p53 tumor suppressor protein (15). I3C can suppress invasion and migration of human breast cancer cells (16) and stimulate IFN-␥ receptor production and IFN-␥ responsiveness (17).…”
mentioning
confidence: 99%
“…A number of studies have shown that I3C induces cell cycle arrest in the G1 phase in cancer cells (8,9), promotes apoptosis (8)(9)(10) and prevents tumor invasion and metastasis (11). It has been found that I3C promotes cell cycle arrest by downregulating cyclin-proteins such as cyclin D1 and cyclin E. Additionally, it is thought that IC3 induces apoptosis by mechanisms that depend on downregulation of the anti-apoptotic genes Bcl-2, Bcl-xL and survivin and by enhancing expression of Bax and by functionally activating caspase-3 and caspase-9 (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies indicated that I3C also induced cell cycle arrest in breast cancer cells and inhibited CdK6, but in high concentration of 200 µM [37][38][39]. In addition, it was demonstrated that I3C activates p53 phosphorylation and disruption of the p53-MDM2 interaction, which releases p53 to induce the p21 CDK inhibition and G1 cell cycle arrest [30,40]. These studies suggested that I3C induced phosphorylation of phosphatidyl-inositol-3-kinase (PI3-K/Akt) family member, ataxia telangiectasia gene that activates p53 through its phosphorelation that induce p21 WAF1 CDK inhibitor and caused a G1 cell cycle arrest.…”
Section: The Anti-cancer Effect Of Indole-diet Derivatives the Effectmentioning
confidence: 99%